Mechanism of enforcement and execution of muslim maintenance order: court - based system - Mohd Saad, Jazilah; Abas, Afridah; Md Hashim, Noraini; Wok, Saodah (International Islamic University Malaysia, 2013)
The weaknesses of the enforcement and execution of a court order always become the reason for noncompliance with court orders issued by the Syariah Court. In other words, the effectiveness of enforcement mechanisms enhances compliance with orders issued by the Syariah Court. Many looked at the weaknesses of enforcement as the weaknesses of the Syariah court as the agency for implementing justice and thus undermining the position of the Islamic law. However, very little attention has been given in the literature as regards what constitutes the mechanism of enforcement and execution of a maintenance order in the Syariah Court. Hence, the purpose of this article is to examine the mechanism used pertaining to non-compliance maintenance orders. The content analysis approach was used as it is appropriate to identify the mechanism used by the selected Syariah courts in settling the enforcement and execution cases. Through the content analysis method, the background of the cases as well as the approach of the court players were identified, respectively. The data from the study then were presented in descriptive form to explain the frequency and the percentage of variables studied. The study suggests that the process of giving judgment relating to maintenance should be improved. In addition, the assimilisation between non-legal and legal processes should be well organised to ensure the effectiveness of the enforcement and execution processes. The weaknesses found should be addressed in future studies to identify the best method for better implementation.